Quality management in higher education from the perspective of institutional isomorphism: a scoping review - Guil Gorostidi, Susana del Carmen; Rubio-Arostegui, Juan Arturo (Frontiers in Education, 2026)
ObjectiveThis article presents a scoping review of academic literature on quality management in higher education, using a neo-institutionalist methodological approach.MethodologyA systematic search was conducted in Scopus, Web of Science, and Google Scholar, complemented by gray literature on university quality from institutional reports, regulations, and documents produced by national and international organizations. The analysis was based on a sample of 113 scientific articles.ResultsThe findings were structured around four axes: (1) theoretical approaches to institutional isomorphism in higher education; (2) quality management and assurance systems; (3) educational policies and their isomorphic effects; and (4) rankings and accreditation processes.ConclusionThe implementation of quality management systems has significantly influenced university governance and academic practices. This review shows that quality assurance processes and governance reforms in higher education not only generate structural convergence but also transform the institutional culture of universities, shaping their values, practices, and priorities. From a neo-institutionalist perspective, both isomorphic pressures and forms of organizational adaptation, negotiation, and resistance were analyzed. Finally, the review highlights the utility of case studies as a methodological tool for examining how institutional arrangements are adopted and reinterpreted in different contexts, enabling a situated connection between theory and organizational reality.